The medical record in mental health - Ramos Pozón, Sergio (Acta Bioethica, 2015)
In this paper we’ll address the issue of medical record in mental health. We structure this paper in four sections. First, we define what is the medical record, which is their content, and how it has to be structured. Second, we expose some deontological principles, ethical principles and ethical virtues to guide the development of the medical record and information management. Third, we analyze the question of who owns the medical record and who can access the information. Finally, we expose some empirical data about the opinion of both patients and professionals about the medical record.